The Life and Times of Nargis - George, T. J. S. (New Delhi HarperCollins Publishers, 1994)
Biography of Nargis Dutt, 1929-1981, Indian motion picture actress.
Include Illustrations and Index
Keywords: Motion picture actors and actresses -- India -- Biography -- Biography